EFEKTIVITAS DAUN SIRSAK TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS BALIBO KABUPATEN BULUKUMBA - Safruddin; Nadia Alfira (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2017)
Hypertension or high blood pressure is an increase in normal blood pressure in blood vessels. Hypertension sufferers in addition to high risk of suffering from heart disease, are also at risk of suffering from other diseases such as nerve and kidney disease. Treatment of hypertension can be done by pharmacological and nonpharmacological methods. Lately the treatment is often done by people who consume herbal plants. The ability of herbs to control hypertension has been proven by our ancestors during various years. One of the herbal plants proven to be able to reduce blood pressure is soursop leaves. Research Objectives is To measure the level of risk of soursop to decrease blood pressure in patients with hypertension in the Work Area of ​​Balibo Health Center, Kindang District, Bulukumba Regency. Research Methods is Quantitative research methods using pre-experimental designs, namely experimental research designs consisting of one group pretest - posttest design. The population in this study were all hypertensive sufferers who were in the work area of ​​Balibo Community Health Center, Kindang District, Bulukumba District, as many as 567 people, 15 samples were taken with successive sampling techniques. The instrument used was a sphygmomanometer, produced in the observation sheet. Research Results is There is a problem with soursop leaves in reducing blood pressure in hypertensive patients in the Puskemsas Balibo work area, Kindang District, Bulukumba Regency. This was discussed with the results of the Wilcoxon systole blood pressure obtained p <α (p = <0.001), and diastolic blood pressure obtained p value <α (p = 0.002). Conclusion: There is an effect of soursop leaves on blood pressure reduction in hypertensive patients in the work area of ​​Puskemsas Balibo, Kindang District, Bulukumba Regency. Suggestion is expected that hypertension sufferers and health workers to use soursop leaves as a treatment for hypertension.